Thermal effect on microchannel electro-osmotic flow with consideration of thermodiffusion - Zhou, Yi (2015)
Electro-osmotic flow (EOF) is widely used in microfluidic systems. Here, we report an analysis of the thermal effect on EOF under an imposed temperature difference. Our model not only considers the temperature-dependent thermophysical and electrical properties but also includes ion thermodiffusion. The inclusion of ion thermodiffusion affects ionic distribution, local electrical potential, as well as free charge density, and thus has effect on EOF. In particular, we formulate an analytical model for the thermal effect on a steady, fully developed EOF in slit microchannel. Using the regular perturbation method, we solve the model analytically to allow for decoupling several physical mechanisms contributing to the thermal effect on EOF. The parametric studies show that the presence of imposed temperature difference/gradient causes a deviation of the ionic concentration, electrical potential, and electro-osmotic velocity profiles from their isothermal counterparts, thereby giving rise to faster EOF. It is the thermodiffusion induced free charge density that plays a key role in the thermodiffusion induced electro-osmotic velocity.